Political legislation cycle in the Czech Republic - Josef Brechler; Adam Geršl (Charles University in Prague, Institute of Economic Studies (IES), 2011)
There is a wide range of theories that try to explain interactions between politics end economy that are referred as political cycles. Majority of these theories aims at analysis of changes in economic outcomes that are related to elections or other phenomena in the political reality. To induce at least some of these changes it is necessary to alter a country's legislation which leads to emergence of political legislation cycles - changes in legislation activity over time in an electoral term. The aim of this paper is to study political legislation cycle in the legislative system of the Czech Republic. Obtained results suggest that elections timing has an impact on legislation activity. As electoral term matures and upcoming elections are getting closer an increase is observed in the legislation activity.
Keywords: H61; H62; C49; 330; political business cycle; economic theory of legislation; voters